A STUDY OF SOLO’S TOURISM PRODUCT POTENTIAL AS HALAL TOURISM DESTINATION IN INDONESIA - Amad Saeroji; Deria Adi Wijaya; Isnaini Wijaya Wardani (Universitas Gadjah Mada, 2018)
Solo or administratively called as Surakarta is a cultural heritage city of the Mataram Kingdom. Tourism of the city shows its development in terms of tourism variety, attractiveness, and amenity. One of the developments leads to halal tourism potentials. The aims of the study are 1) to identify the halal tourism potentials concerning on 4A approach (attraction, amenity, accessibility, and ancillary) as major components of tourism; 2) to examine the opportunities of halal tourism destination to meet the criteria set by GMTI (Global Muslim Travel Index). This study uses a qualitative method. Data were collected through interview, observation, literature review and documentation. The identification of halal tourism products leads to substantive object as basic for reviewing tourism development opportunities. The collected data was analyzed into four 4A variables based on Miles and Hubberman analysis to be presented descriptively. The results showed that halal tourism potentials based on carrying capacity of tourism products is high. The existence of attractions, amenity, accessibility and tourism institution throughout city and the surrounding areas become an important element in the development of halal tourism. As a halal tourism destination, Solo has significant opportunities, especially the availability of amenity in the form of sharia hotels, restaurants and community-based cultural attraction that has grown in line with growth of world’s halal tourism. The accessibility and ancillary variables are still being homework for halal tourism stakeholders to meet the standards set by GMTI. The variables that make Solo feasible for halal destination are in attraction and amenity while accessibility and institutional sector still requires serious handling if referring to the needs of Muslim tourists.